Design of Android and IoS Applications for Mobile Health Monitoring Devices - Ade Silvia Handayani; Anisah Fadhilah; Ibnu Ziad; Nyayu Latifah Husni; Sri Chodidjah; Mega Hasanul Huda; Nur Agustini; Mieska Despitasari; Riswal Hanafi Siregar (Advance Sustainable Science Engineering and Technology, 2023)
This research proposes a multifunctional wireless health monitoring tool with a display for Android and iOS devices. This research aims to develop a realistic solution for real-time and conveniently accessible health monitoring via mobile devices. The device allows users to test and track health factors such as heart rate, blood pressure, blood oxygen levels, body temperature, and blood glucose. It collects data properly by using wireless technology and sensors. The data is subsequently supplied to the appropriate apps on Android and iOS devices. The data is presented visually in the program, making it instructive and user-friendly. The device's development technique involved extensive testing and validation against established comparators to assure accuracy. The results of this study show that this digital, multi-purpose health monitoring device works well and reliably to give real-time health information. This innovation promotes health monitoring and digital health information access.